Fatores associados à adesão à estratégia de contagem de proteínas e gorduras por adultos com diabetes mellitus tipo 1 - COSTA, Juliana Carvalho da (2024)
Adherence to treatment for type 1 diabetes mellitus (T1DM) requires the patient to be disciplined in carrying out various behaviors, such as insulin application, physical exercise, frequent blood glucose monitoring, adherence to healthy habits, Carbohydrate Counting (CC) and protein and fat counting, which allows individuals to have better glycemic and metabolic control. The aim of this study was to analyze the factors associated with adherence to the protein and fat counting strategy in adults with T1DM. This study adopted a cross-sectional approach and was conducted from November 2021 to June 2022, using an online form, including questions about CC, clinical and anthropometric data, socioeconomic and demographic issues, and follow-up with health professionals. Pearson's chi-square test was applied with analysis of adjusted residuals and the binomial logistic regression test using SPSS software, v. 24.0, considering p<0.05 as statistical significance. Of the 173 participants, the majority (32.4%) knew what protein and lipid counting was, but did not know how to do it. There was an association between protein and lipid counting and having a university degree (p=0.002), having an income of more than 3 minimum wages (p=0.002) and having adequate glycated hemoglobin (HbA1c) (p<0.000). Having a protein and lipid count increased the chance of having an adequate HbA1c by 4.3 times. Having a protein and lipid count was a predictor of having adequate HbA1c. The results showed that the practice of counting proteins and fats is also important as a strategy to optimize glycemic control. Most of the participants are aware of protein and fat counting, but they don't know how to do it, which indicates the need to invest in diabetes education.